Enhancing Language Skills of 4-5 Year-Old Children Using Flip Chart Media at TK Darussalam Sidowayah Beji - Dina Zuhrufia; Muhamad Mukhlason; Nafila Firdausiyah (RETORIKA: Jurnal Ilmu Bahasa, 2023)
TK Darussalam Sidowayah Beji faces challenges in the language proficiency of children, as some still use local languages such as Javanese and Madurese, affecting their language skills during learning. Despite employing various media to enhance the language skills of 4-5-year-old children, research indicates that these media are seldom utilized by teachers, resulting in inadequate language development. This study aims to improve the language proficiency of 4-5-year-old children using the Flip Chart media at TK Darussalam Sidowayah Beji. The research employs Action Research (PTK) with data collection techniques such as observation, interviews, and documentation. The study includes 21 subjects, comprising 12 boys and 9 girls. Results from three cycles show progress: the first cycle achieved 24.00%, engaging children to identify images and text on the Flip Chart; the second cycle reached 33.00%, challenging children to complete sentences with vowels related to the written text beneath engaging images; and the third cycle achieved 95.00%, involving children in mimicking or role-playing based on the images presented on the Flip Chart. The Flip Chart not only enhances language but also makes learning enjoyable for 4-5-year-olds.